PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGASI (GI) DAN KREATIVITAS BELAJAR TERHADAP HASIL BELAJAR BIOTEKNOLOGI - Zubaidi, Zubaidi; Asyhar, Rayandra; Syamsurizal, Syamsurizal (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2013)
The purpose of this study was to determine: (1). The relationship between the creativity of students with learning outcomes Biotechnology. (2). The difference in learning outcomes are taught using cooperative learning model Group Investigation when compared with the conventional model. and to determine how much influence it in a mathematical equation. The subjects were students of class IX, which consists of two classes that exist in the SMP 14 Batang Hari first semester of the academic year 2011 / 2012. The number of students of class IX is 60 people. Class has been divided by the school since the beginning of the class consisting of 30 people IXA, IXB class of 30 people. Members direndominasi subject can not because they are made in such a way from school, academically have average ability of each class is the same so it is considered homogeneous. This research was conducted by using a quasi-experimental type (quasi experiment) with the experimental design consists of classes and control classes.Based on the results of the study showed that: First, the influence of creativity learning on learning outcomes of biotechnology with learning outcomes, namely 7.78 to 7.32 in the experimental class and the control class. Second, the result shows that the statistical processing of F = 182.114 and table F, Fï¡ï€®ï€±ï€®a (n-1)-1 = F.1.1.81 = 2,77 for F count > Ftabel or 182.114 > 2.77 then there is a difference learning outcomes of students who were taught with the model group when compared with the conventional investigate. The conclusion of this study are: (1) There is a significant effect on learning outcomes learning creativity Biotechnology. (2) There are differences in learning outcomes that learned by using cooperative learning model Group Investigation when compared with the conventional model. Keyword: type of investigation group, creativity, learning outcome.